The German Mezzogiorno? Supplements to the Natural History of East German Regional Development - Horváth, Gyula (Discussion Papers, 2022)
Every country in the world is characterised by a heterogeneous spatial structure and the existence of regional disparities, and the aim of regional policy is to moderate these inequalities in the spatial development of economic activities. There are certain countries where spatial disparities are extremely large and areas lagging behind belong to one specific geographic area which feature a dual economic structure. There are, specifically, two large areas amongst the developed countries of the European Union whose economic performance lags behind the EU average and whose development paths are unique in many ways. An investigation into the unique development specifics of these two large, but coherent, territories – the regions of Southern Italy (the Mezzogiorno) and Eastern Germany – has attracted the interest of regional scientists for a long time. Today, the name “Mezzogiorno” is synonymous with long-term underdevelopment, whilst the other large area in question was reintegrated into the “mother country” after half a century of separation. Underdevelopment can be detected in almost all elements of the economy, the infrastructure and living conditions. Post-WW2, political constraints forced the German states to strike out along new paths. Five East German Länder and East Berlin were under Soviet occupation, and the planned economy of the German Democratic Republic created in 1949 gave rise to specific patterns of socio-economic development. The development rate of the previously advanced German provinces was considerably slower in the newly formed state than in West German Länder, and in the year of German reunification, labour productivity indices of East German areas were one-third of the West German average. Nevertheless, in the first years of the 2000s, the East German states showed more rapid convergence with the developed regions’ average values than did the Southern Italian regions. The present paper aims to explore how various eras have left their mark on the recent regional development of East German states (Länder), what kinds of spatial transformation have occurred, what factors can be detected behind these changes and how spatial disparities have evolved in this vast, but backward, area in developed Europe.